2023
DOI: 10.3390/ma16051834
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity and Bioavailability of Nickel Nanoparticles Compared to Nickel Microparticles in Mice

Abstract: Metal allergy is a common disease that afflicts many people. Nevertheless, the mechanism underlying metal allergy development has not been completely elucidated. Metal nanoparticles might be involved in the development of a metal allergy, but the associated details are unknown. In this study, we evaluated the pharmacokinetics and allergenicity of nickel nanoparticles (Ni-NPs) compared with those of nickel microparticles (Ni-MPs) and nickel ions. After characterizing each particle, the particles were suspended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…On the contrary, the combustion of nickel-containing fossil fuels, nickel-manufacturing industries and the utilization of nickel products has induced the excessive release of nickel compounds and nanoparticles into the environment, leading to hazardous health effects on organisms [39,40]. Previous studies have demonstrated that nickel nanoparticles have more intense toxicity and stronger sensitization than microparticles [29,41]. The liver is the major biological filtration barrier organ responsible for the sequestration and biodegradation of exogenous substances, medicines and nanomaterials [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the combustion of nickel-containing fossil fuels, nickel-manufacturing industries and the utilization of nickel products has induced the excessive release of nickel compounds and nanoparticles into the environment, leading to hazardous health effects on organisms [39,40]. Previous studies have demonstrated that nickel nanoparticles have more intense toxicity and stronger sensitization than microparticles [29,41]. The liver is the major biological filtration barrier organ responsible for the sequestration and biodegradation of exogenous substances, medicines and nanomaterials [37].…”
Section: Discussionmentioning
confidence: 99%
“…NiNPs in the bloodstream are mainly detained by the liver [27][28][29]. Recent reports indicated that nickel and nickel-containing nanoparticles exhibited liver injury in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nickel NPs have been shown to cause hypersensitivity reactions. On subsequent exposures, the body reacts more strongly, leading to severe inflammation and other allergic symptoms [136].…”
Section: Systemic Toxicitymentioning
confidence: 99%